A novel approach identifies new differentially methylated regions (DMRs) associated with imprinted genes - Choufani, Sanaa; Shapiro, Jonathan S.; Susiarjo, Martha; Butcher, Darci T.; Grafodatskaya, Daria; Lou, Youliang; Ferreira, Jose C.; Pinto, Dalila; Scherer, Stephen W.; Shaffer, Lisa G.; Coullin, Philippe; Caniggia, Isabella; et al.

(untitled) (Genome Research, 2011)
Imprinted genes are critical for normal human growth and neurodevelopment. They are characterized by differentially methylated regions (DMRs) of DNA that confer parent of origin-specific transcription. We developed a new strategy to identify imprinted gene-associated DMRs. Using genome-wide methylation profiling of sodium bisulfite modified DNA from normal human tissues of biparental origin, candidate DMRs were identified by selecting CpGs with methylation levels consistent with putative allelic differential methylation. In parallel, the methylation profiles of tissues of uniparental origin, i.e., paternally-derived androgenetic complete hydatidiform moles (AnCHMs), and maternally-derived mature cystic ovarian teratoma (MCT), were examined and then used to identify CpGs with parent of origin-specific DNA methylation. With this approach, we found known DMRs associated with imprinted genomic regions as well as new DMRs for known imprinted genes, NAP1L5 and ZNF597, and novel candidate imprinted genes. The paternally methylated DMR for one candidate, AXL, a receptor tyrosine kinase, was also validated in experiments with mouse embryos that demonstrated Axl was expressed preferentially from the maternal allele in a DNA methylation-dependent manner.